Irresponsible Lending? A Case Study of a U.K. Credit Industry Reform Initiative - Richards, Maria (Journal of business ethics, 2008)
There are major concerns about the level of personal borrowing, particularly sourced from credit cards. This paper charts the progress of an initiative to create a Responsible Lending Index (RLI) for the credit industry. The RLI proposed to voluntarily benchmark lending standards and promote best practice within the credit industry by involving suppliers of credit, customer representatives and regulators. However, despite initial support from some banks, consumer bodies and the Chair of the Treasury Select Committee, it failed to gain sufficient support from financial institutions in its original format. The primary reasons for this were related to the complexity of building such a robust index and the banks trade body’s fear of exposing its members to public scrutiny. A revised alternative, the Responsible Lending Initiative, was proposed which took into account these concerns. However, the Association of Payment Clearing Service (APACS), the trade body of the credit industry, then effectively destroyed the proposal. This article describes an attempt to address the challenges in the credit card industry with the initiation of the RLI, reflected in stakeholder discourse and in the context of a wider concern expressed by the involved stakeholders in terms of the need for greater responsibility in the banking industry’s lending practices.